Low Serum Beta-2 Microglobulin Level: A Possible Biomarker for Sarcopenia in the Elderly Population - Ceren Kanat Sahin; Burak Mete; Hakan Demirhindi; Gülşah Yaşa Öztürk; Esra Ateş Bulut; Erkan Kozanoğlu; Gülçin Dağlıoğlu; Bülent Kaya; Ertuğrul Bayram (Medicina)
Background and Objectives: One of the most critical problems regarding sarcopenia is the difficulty of the diagnosis process. This study aimed to determine the prevalence and investigate the role of serum beta-2 microglobulin level as a biomarker for diagnosing sarcopenia. Materials and Methods: This nested case–control study was conducted between 2023 and 2024 on 251 older adults. Muscle strength was measured using a hand dynamometer, and muscle mass was assessed using the bioelectrical impedance method. Individuals with low muscle strength and low muscle mass were accepted as having definitive sarcopenia. Results: The mean age of the 251 older adults included in the study was 72.19 ± 6.11 years. The prevalence of sarcopenia in individuals aged 65 years and over was found to be 5.2%. Serum beta-2 microglobulin levels were statistically significantly lower in sarcopenic participants compared to the control group (p = 0.002). The optimal cut-off value for serum beta-2 microglobulin level was 2.26 mcg/mL, and values lower than this point were found to be diagnostic for sarcopenia. Regarding the cut-off value, the sensitivity was 92.31% and the specificity was 80.77%, the positive predictive value was 70.59%, the negative predictive value was 95.45%, the Youden index was 0.731, and the area under the curve value was 0.901. Individuals who had beta-2 microglobulin levels below 2.26 mcg/mL were found to have a 10.75 times higher risk of sarcopenia. Conclusions: A low serum beta-2 microglobulin level has the potential to be an important candidate biomarker for the diagnosis of sarcopenia.